The Process of Ideological Transformation Society in Soviet Armenian in 1930-1980 - Zohrabyan, Eduard (History and Culture, 2021)
The article analyzes the process of development of Armenian studies in Soviet Armenia and the ideological transformations of society under its influence in 1930-1980. The question is considered in the context of the changes that took place in the socio-economic and domestic political life of the Soviet society in the mentioned historical period. The manifestations of national thinking and mentality that were identified on the basis of Armenian studies in the previous period, during the two post-war decades, themselves turned into new achievements in the field of Armenian studies. History, which has received a national image, has become personified, and the understanding of the awareness of national identity has deepened even more. The discussion of episodes of the struggle for national liberation, as well as the discussion of forbidden topics of the Armenian Genocide, has matured into Armenian political thought, and the beginning of political Armenian studies has been laid. Armenian studies during this period contributed to the motivation of the society for the national struggle.